1992
DOI: 10.1136/pgmj.68.799.378
|View full text |Cite
|
Sign up to set email alerts
|

Congenital left ventricular diverticula: a rare cause of sudden cardiac death

Abstract: Summary:Congenital left ventricular diverticula are a rare cause of sudden cardiac death. We describe the first reported case of ventricular fibrillation in association with congenital diverticula of the heart. The diagnosis of left ventricular diverticula was made by cardiac catheterization and confirmed by magnetic resonance imaging. Treatment was initiated with anti-arrhythmic and anticoagulant drugs to prevent life-threatening arrhythmias and emboli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…11 Echocardiography can detect large left ventricular diverticula, but it is difficult to detect a small one by the conventional 2-D method. 7 Delineation of the endocardial borders is often impossible with conventional echocardiography because of side-lobe or clutter artifacts. The newly developed technique of second harmonic imaging produces ultrasound images using only signals with frequencies twice those of the transmitted ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Echocardiography can detect large left ventricular diverticula, but it is difficult to detect a small one by the conventional 2-D method. 7 Delineation of the endocardial borders is often impossible with conventional echocardiography because of side-lobe or clutter artifacts. The newly developed technique of second harmonic imaging produces ultrasound images using only signals with frequencies twice those of the transmitted ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The differential diagnosis of symptomatic ventricular embolic events, tachyarrhythmias or heart failure of unknown origin should include congenital ventricular aneurysms or diverticula and it is important to diagnose this anomaly even if the patient is asymptomatic. Left ventriculography is more useful than magnetic resonance imaging or echocardiography for detecting this anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…A nonsurgical strategy with careful follow-up has been chosen in many case reports [42, 49, 50, 52, 56, 60, 63, 65, 75, 86] and is supported by a series of 16 patients [6]. In this series, an uneventful course could be demonstrated in 94% of the patients over a period of up to 127 months (mean 61 months), with an event rate of approximately 1.2% per year.…”
Section: Therapymentioning
confidence: 99%
“…Most LVD were encountered in isolation and only two patients had multiple diverticula in this series of 94 cases . A few isolated reports describe multiple LVD detected through various imaging modalities . Alkan et al reported a 33‐year‐old female presenting with an ischemic cerebrovascular accident and was found to have multiple LVD on echocardiography.…”
Section: Discussionmentioning
confidence: 79%